Eucalyptus Plantation benefits to patch size and shape of forested areas in southeast atlantic forest - Sapucci, Gabriela Ribeiro [UNESP]; Negri, Rogério Galante [UNESP]; Massi, Klécia Gili [UNESP]; Alcântara, Enner Herenio de [UNESP] (FapUNIFESP (SciELO), 2022)
The adoption of mixed plantation systems (exotic and native species) is viable and represents an important alternative in the context of forest and landscape restoration. This study evaluated whether Eucalyptus cultivation is associated with changes in native forest cover and fragment connectivity in the region from 1987 to 2017. The study region (Southeast Atlantic Forest) has been undergoing a forest transition process. Based on land use/land cover maps obtained from satellite images and a pair-wise comparison, it was detected that the dynamics in one land cover were not necessarily associated with the other one. It was verified an increase in Eucalyptus cover since 2007, possibly related to the New Forest Code that allows the use of exotic species in reforestation, provided it does not exceed 50% of the total area. An increase in the native vegetation cover was also observed, highlighting the importance of restoration actions and national regulations. In addition, forest patches were larger and less complex with Eucalyptus presence, indicating that this land cover is potentially beneficial for the landscape connectivity.

A adoção de sistemas de plantios mistos (espécies exóticas e nativas) é viável e representa uma importante alternativa no contexto da restauração florestal e paisagística. Este estudo avaliou se o cultivo de Eucalyptus está associado a mudanças na cobertura florestal nativa e conectividade de fragmentos na região de 1987 a 2017. A região de estudo (Mata Atlântica do Sudeste) vem passando por um processo de transição florestal. Com base em imagens de satélite, mapas de uso e cobertura da terra e uma comparação pareada, verificamos que a dinâmica em uma cobertura da terra não estava necessariamente associada à outra. A partir de 2007 verificamos um aumento da cobertura de Eucalyptus, possivelmente relacionado às regras do Novo Código Florestal, que permite o uso de plantios de espécies exóticas para recomposição da vegetação, não ultrapassando 50% da área total, e aumento da cobertura vegetal nativa, destacando o importante papel de várias ações de restauração que ocorrem na região e algumas regulamentações nacionais. Além disso, remanescentes florestais foram maiores e menos complexos com a presença de Eucalyptus, indicando que essa cobertura do solo é potencialmente benéfica para a conectividade dessa paisagem.
Benefícios do plantio de Eucalyptus para o tamanho e forma de fragmentos de áreas florestais na mata atlântica do sudeste
Keywords: Floresta tropical; Silvicultura; Conectividade; Tropical forest; Silviculture; Connectivity